Scanning Electron Microscopy Morphology of Metal Salts of Saturated Aliphatic Acids: Sodium Ion Results Branched Fibrous Image - Kang, Min Su; Keum, Gyochang; Hwang, Kwang-Jin (대한화학회, 2021)
Sodium ion leads a fibrous SEM image for the metal salts of saturated aliphatic acids (C12-24).